Liberdade, propriedade e estado: Kant e Nozick em diálogo - Coelho, Vanderson Lopes (2023)
In the context of modern and contemporary legal philosophy, this research offers, at first, a reconstruction of the thought of Immanuel Kant, philosopher of the 18th century and great exponent of the Enlightenment, with regard to the justification of the State as a necessary condition to guarantee freedom and private property of individuals, making it peremptory. It approaches these ideas in Robert Nozick, philosopher of the 20th century, and great exponent of libertarianism, in order to question Kant's position while aiming, at the same time, to provide Kantian answers. The research shows how Immanuel Kant starts from certain premises in favor of individual freedom. It deals with the conception of the state of nature in Kant and Thomas Hobbes and Kant's theory of property. It also deals with the social pact in Kant, comparing it with that of Hobbes and John Locke, and how the State should be for Kant. In a second moment, the research enlightens certain aspects of Robert Nozick's philosophy, showing how the philosopher understands, under the light of Lockean principles, that human beings have rights in the state of nature. It shows that for Nozick individuals could, in the state of nature, hire services from private protection agencies in order to protect their rights, without having to resort to a State. It shows that for Nozick, from the protection agencies an ultra-minimal State could emerge and which would become a minimum. The research also shows that the only State that is justified for Nozick is the minimal State, which is limited to protecting the rights of individuals and that the State performing other functions is not justified. Finally, it deals with questions that can be asked, from Nozick's perspective, to Kant's ideas aiming at developing Kantian answers.